The shift of "Self" and "Other" portrayed in the Novels of Three South African Nobel Laureates : J.M. Coetzee, Doris Lessing and Nadine Gordimer - Mah-Zareen (BRAC University, 2015)
This thesis is submitted in partial fulfillment of the requirements for the degree of Master of Arts in English, 2015.